Does the central bank directly respond to output and inflation uncertainties in Turkey? - Pelin Oge Guney (Central Bank Review (CBR), 2016)
This paper investigates the role of inflation and output uncertainties on monetary policy rules in Turkey for the period 2002 : 01–2014 : 02. In the literature it is suggested that uncertainty is a key element in monetary policy, hence empirical models of monetary policy should regard to uncertainty. In this study, we estimate a forward-looking monetary reaction function of the Central Bank of the Republic of Turkey (CBRT). In addition to inflation and output gap variables, our reaction function also includes both the inflation and output growth uncertainties. Our results suggest that the Central Bank of the Republic of Turkey (CBRT) concerns with mainly price stability and significantly responds to inflation and growth uncertainties.
Keywords: E43; E52; 330; Uncertainty; Taylor rule; Monetary policy; Turkey; GMM